IMPLEMENTATION OF ELECTRONIC CUSTOMER RELATIONSHIP MANAGEMENT IN THE DONATION SERVICE INFORMATION SYSTEM - Ali Ibrahim; Beriadi Agung Nur Rezqeb (Kresnamedia Publisher, 2022)
LAZNAS LMI Regional Office of South Sumatra is an institution engaged in the field of religion and humanity. One of the services provided by the LMI Regional Office of South Sumatra is a donation service. However, the service is still not effective and efficient. Based on the results of the questionnaire on donation services at the LMI Regional Office of South Sumatra, the calculation results. obtained Net Promoter Score1 of -61.6% which indicates a negative value. This shows the need to improve donation services in order to create loyalty. The E-CRM concept aims to provide satisfaction and increase loyalty. Therefore we need a donation service information system that can make it easier for both LMI and donors. As well as a measurement that measures the loyalty of donors using the Net Promoter Score calculation method and the FAST system development method. From the measurement results of Net Promoter Score2, the calculation results are 77%, this shows that the loyalty of donors has increased towards the improvement of donation services at LMI Regional Office of South Sumatra.